"I will speake of that subject no more": the Whig legacy of Thomas Hobbes. Issue 2 (3rd April 2019) - Carmel, Elad
ABSTRACT: Hobbes left a complicated legacy for the English Whigs. They thought that his Leviathan was all too powerful, but they found other elements in his thought more appealing – mostly his anticlericalism. Still, the precise relationship between Hobbes and the Whigs has remained underexplored, while some still argue that Hobbes was simply too much of an absolutist for the Whigs to rely on his political ideas. This article attempts to show that Hobbes was, in fact, recruited by proto- and early Whigs for their causes. It shows how Hobbesian ideas were used in the toleration debates of the 1660s and 1670s, and even in debates on human reason and liberty of conscience. Then it demonstrates how similar Hobbesian principles, and even phrases, were used subsequently in the formative years of Whiggism from the 1680s to the 1720s, by thinkers who were worried, as Hobbes was, about the political aspirations of the Church. By collecting a series of prominent thinkers who are associated with Whiggism and who engaged with Hobbes in various ways – including Buckingham, Marvell, Cavendish, Warren, Blount, Tindal, Trenchard and Gordon – this article shows that Hobbes was employed systematically in the service of Whig causes, such as limited toleration, civil religion and an opposition to religious persecution.